2014
DOI: 10.1074/mcp.m114.041228
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Landscape of Hsp27 Reveals New Cellular Processes such as DNA Repair and Alternative Splicing and Proposes Novel Anticancer Targets

Abstract: Previously, we identified the stress-induced chaperone, Hsp27, as highly overexpressed in castration-resistant prostate cancer and developed an Hsp27 inhibitor (OGX-427) currently tested in phase I/II clinical trials as a chemosensitizing agent in different cancers. To better understand the Hsp27 poorly-defined cytoprotective functions in cancers and increase the OGX-427 pharmacological safety, we established the Hsp27-protein interaction network using a yeast two-hybrid approach and identified 226 interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 79 publications
0
46
0
1
Order By: Relevance
“…However, unlike the UBR1 family, HUWE1 is a giant (450 kD) ubiquitin ligase, and in addition to the HECT ubiquitin ligase domain, it contains many protein-protein interaction motifs. Among the reported interactions, it is noteworthy that HUWE1 was identified as a component of the Hsp27 interactome [34]. This provides a possible explanation for the hydrophobic nature of the identified ‘degron’ on HUWE1 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the UBR1 family, HUWE1 is a giant (450 kD) ubiquitin ligase, and in addition to the HECT ubiquitin ligase domain, it contains many protein-protein interaction motifs. Among the reported interactions, it is noteworthy that HUWE1 was identified as a component of the Hsp27 interactome [34]. This provides a possible explanation for the hydrophobic nature of the identified ‘degron’ on HUWE1 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence show that AS of AR is a key capability of cancer cells to evade the normal activation of the pathway [136]. absence of Hsp27, strongly supports the involvement of Hsp27 in differential splicing events [98]. High-throughput analyses of PC samples have revealed more than 200 genes whose AS is differentially regulated.…”
Section: Alternative Splicingmentioning
confidence: 95%
“…Notably, Hsp27 belongs to the 1% of genes overexpressed during CR progression [94,95] and is associated with poor prognosis and treatment resistance [97]. We also recently demonstrated that Hsp27 is a multifunctional protein capable of interacting with a great number of partner proteins to protect cells from lethal conditions [98]. We showed that the Hsp27-interacting protein TCTP is involved in Hsp27 cytoprotection in CRPC [99].…”
Section: Anti-apoptotic Proteins Overexpressionmentioning
confidence: 95%
“…Although HUWE1‐dependent degradation of unassembled proteins is linked to the Ub‐selective chaperone p97, the possible involvement of other chaperones engaged in recognizing and presenting misfolded HUWE1 targets is not addressed yet. A recent proteomic study identified HUWE1–Hsp27 interaction, which might link HUWE1 to chaperone‐dependent degradation of hydrophobic polypeptides .…”
Section: Different Strategies For Targeting Misfolded Proteins In Thementioning
confidence: 99%